2017
DOI: 10.1177/2158244017712776
|View full text |Cite
|
Sign up to set email alerts
|

Threat-Related Attentional Biases in Police Officers and Martial Artists: Investigating Potential Differences Using the E-Stroop and Dot Probe Task

Abstract: In this study, we investigated the possible development of threat-related attentional bias due to the work as a police officer. For this purpose, we compared four groups, differing with regard to their experience in policing and martial arts: (a) police officers with no experience in martial arts (n = 74), (b) martial artists (n = 50), (c) police officers with martial arts experience (n = 33), and (d) a control group (n = 48). Participants completed the Dot Probe Task, the Emotional Stroop Task, and the State-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 103 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…Only five original studies were found, which was not expected. Our main findings are that all studies analyzed how MA/F/CS can help police officers in carrying out their duties even in stressful situations (RENDEN et al, 2015;RENDEN et al, 2015a;TORRES, 2018;STALLER et al, 2017) and how its practice can prevent injuries and reduce medical certificates (JIMÉNEZ et al, 2020). Figure 1 illustrates the main findings of this study.…”
Section: Sourcesmentioning
confidence: 59%
“…Only five original studies were found, which was not expected. Our main findings are that all studies analyzed how MA/F/CS can help police officers in carrying out their duties even in stressful situations (RENDEN et al, 2015;RENDEN et al, 2015a;TORRES, 2018;STALLER et al, 2017) and how its practice can prevent injuries and reduce medical certificates (JIMÉNEZ et al, 2020). Figure 1 illustrates the main findings of this study.…”
Section: Sourcesmentioning
confidence: 59%
“…The martial arts offer a well-developed platform to engage in such embodied practice [4]. Traditional martial artists are arguably extremely adept in the art of embodied self-regulation [51], evidenced by research that points to superior attentional, motivational switching and integrative capacities [52][53][54], as well as greater impulse control and distress tolerance in threatening situations [55,56]. Their training requires them to develop deeply embodied distress tolerance abilities in the face of antagonistic relational threats [4,6,57] and respond in a prosocially-driven co-regulatory manner [51,58,59], that is focused on neutralising/halting actions that cause suffering and reestablishing relational harmony [5,60,61].…”
Section: The Potential Of Traditional Martial Arts For Therapist Self...mentioning
confidence: 99%
“…Recent fMRI research into the effects of mind-body training through Budo in Kendo practitioners on the motivation network supports this notion, in that “resting vs. attentionally-driven” switching/change of motivation can be trained and becomes more efficient (Fujiwara et al, 2019 ), which is indicative of an unmoving/undisturbed/unfettered mind (Wilson and Takuan, 2012 ) which better affords an appropriate physical response. Research also suggests that martial artists are more endogenously prepared to engage with and respond to uncertainty (Johnstone and Marí-Beffa, 2018 ) and are more distress tolerant when faced with and despite repeated exposure to threatening situations (Staller et al, 2017 ), as well-having greater sustained attentional abilities and impulse control (Sánchez-López et al, 2013 ; Sánchez-Lopez et al, 2016 ). All of this combines to lead to skillful action that is reasoned, assertive and conflict-ending rather than mindlessly aggressive and designed to excessively hurt another.…”
Section: Martial Arts As Radically Embodied Compassionmentioning
confidence: 99%